A DFT study of H2O dissociation on metal‐precovered Fe (100) surface. (22nd January 2018) - Zhang, Chuan‐Hui; Chen, Bao; Sun, Dong‐Bai
Abstract : The H2 O adsorption and dissociation on the Fe (100) surface with different precovered metals are studied by density functional theory. On both kinds of metal‐precovered surface, H2 O molecules prefer adsorb on hollow sites than bridge and top sites. The impurity energy difference is proportional to the adsorption energy, but the adsorbates are not sensitive to the adsorption orientation and height relative to the surface. The Hirshfeld charge analysis shows that water molecules act as an electron donor while the surface Fe atoms act as an electron acceptor. The rotation and dissociation of H2 O molecule occur on the Co‐ and Mn‐precovered surfaces. Some H2 O molecules are dissociated into OH and H groups. The energy barriers are about 0.5 to 1.0 eV, whose are consistence with the experimental data. H2 O molecules can be dissociated more easily at the top site on Co‐precovered surface 1 than that at bridge site on Mn‐precovered surface 2 because of the lower reaction barrier. The dispersion correction effects on the energies and adsorption configurations on Co‐precovered surface 1 were calculated by OBS + PW91. The dispersion contributions can improve a bit of the bond energy of adsorbates and weaken the hydrogen bond effect between adsorption molecules a little.